The Indigenous Community and Our Law - Pásara, Luis (1968)
This article examines the situation of indigenous communities in Peru, focusing particularly on the legal framework that governs them. The author points out that the legislation that regulates indigenous communities presents a serious problem, namely the fact that it ignores the concrete reality of the different indigenous communities located throughout the territory; likewise, this regulation is inadequate, since it is characterized by a protectionist or guardianship character, instead of promoting the development of the peasant community. In order to better understand the problem, the author not only conducts a brief analysis of the legal nature of the indigenous community, highlighting that it is fundamentally agrarian, but also examines the socio-legal reality of the different indigenous communities, noting that each of them has cultural, economic, social and demographic characteristics that distinguish them from themselves and the rest of the country, a fact that poses a real challenge to national legislation. The article concludes by pointing out the need to develop policies that provide the normative framework, recognizing that the state response to this serious problem requires different axes of intervention and not only a legal approach that can adapt to the context of indigenous communities.